Epidermolysis bullosa simplex with PLEC mutations: new phenotypes and new mutations. (25th March 2013) - Charlesworth, A.; Chiaverini, C.; Chevrant‐Breton, J.; DelRio, M.; Diociaiuti, A.; Dupuis, R.P.; El Hachem, M.; Le Fiblec, B.; Sankari‐Ho, A.M.; Valhquist, A.; Wierzbicka, E.; Lacour, J.P.; et al.
Summary Background Genetic mutations in the plectin gene (PLEC) cause autosomal recessive forms of epidermolysis bullosa simplex (EBS) associated with either muscular dystrophy (EBS‐MD) or pyloric atresia (EBS‐PA). Phenotype–genotype analysis has suggested that EBS‐MD is due mostly to genetic mutations affecting the central rod domain of plectin, and EBS‐PA to mutations outside this domain. Objectives This study aimed to describe new phenotypes of patients with EBS‐MD and EBS‐PA, to identify novel PLEC mutations and to establish genotype–phenotype correlations. Methods Seven patients with a suspicion of EBS linked to PLEC mutations were included. A standardized clinical questionnaire was sent to the physicians in charge of each patient. Immunofluorescence studies of skin biopsies followed by molecular analysis of PLEC were performed in all patients. Results We report the first case of nonlethal EBS‐PA improving with age, the first multisystemic involvement in a patient with lethal EBS‐PA, and the first patients with EBS‐MD with involvement of either the bladder or oesophagus. Eleven novel PLEC mutations are also reported. Conclusions Our results confirm that EBS‐PA is linked to mutations in the distal exons 1–30 and 32 of PLEC. Long‐term survival is possible, with skin improvement, but a delayed onset of MD is probable. While EBS‐MD is linked to PLEC mutations in all exons, in most cases one of the mutations affects exon 31. The precocity of MD seems to be linked to the type and localization of the PLEC mutation(s), but no correlation with mucosal involvement has been found.